Teachers’ Experiences of Presence in Their Daily Educational Practice - Edith Roefs; Yvonne Leeman; Ida Oosterheert; Paulien Meijer (Education Sciences, 2021)
In the context of education, ‘presence’—a state of alert awareness, receptivity and connectedness to what is happening in class—is related to depth of insight into the situation, and to more opportunities for action. Presence is mainly conceptualized in philosophical and theoretical terms and idealistic accounts. This study aims to gain understanding of teachers’ experiences of the emergence and manifestation of their own and students’ presence in their daily educational practice and insight into the significance they attach to presence. This is relevant because presence may contribute to teachers’ reflection-in-action and their ability to respond to classroom situations. Using a phenomenological approach, we interviewed 12 secondary teachers in the Netherlands about their lived experiences of presence. The participants relate presence to being concurrently attentive and aware of students and of themselves, to lively interaction, to relevant education and to students’ deep understanding of the subject matter and students’ personal development. In the discussion of the significance of presence, we suggest that research on presence might promote our understanding of how teaching may afford the coming together of students’ academic learning and their personal development. In addition, our findings are related to teachers’ professionalism and personal professional fulfillment.